Electronic court system (E-court): development and implementation in the Malaysian courts and other jurisdictions - Mohamed, Duryana (Sweet & Maxwell Asia, 2011)
Electronic court system or e-court is one of the projects under the e-government flagships. Originally, the idea of having the e-court system was mooted in 1996 but due to economic crisis in late 1990s, the idea was finally materialised in May 2002. At present, the Malaysian courts consist of an audio recording system, verbatim recording of court cases, video recording and video conferencing. It also has the Case Management System (CMS), which includes the Electronic Filing System (EFS) and the Court Recording and Transcription (CRT) system. However, there is no specific rule governing the practice and implementation of e-court system in Malaysia. This paper discusses the development and implementation of e-court system in Malaysia and the available laws governing the system. As comparison, the practice and procedures on e-court system in Singapore, the United Kingdom and Australia will also be discussed. It is submitted that there is a need to review the existing court rules and Practice Direction in order to achieve effective implementation of e-court system in Malaysia.